Influence of sub-monolayer quantities of carbon nanoparticles on the melting and crystallization behavior of polyamide 12 powders for additive manufacturing. (March 2021) - Sommereyns, Alexander; Hupfeld, Tim; Gann, Stan; Wang, Tao; Wu, Cunchen; Zhuravlev, Evgeny; Lüddecke, Arne; Baumann, Stéphanie; Rudloff, Johannes; Lang, Marieluise; Gökce, Bilal; Barcikowski, Stephan; et al.
Abstract: In this paper, the influence of 0.005 vol% and 0.05 vol% of carbon nanoparticles on the surface of polyamide 12 powder particles by dry coating and colloidal additivation is evaluated in great detail concerning thermal and microstructural properties. The dispersion of the nanoparticles on the polymer surface influences the flowability of the feedstock powder already during the additivation process. When analyzing the composite powders dynamically and isothermally with fast scanning and differential scanning calorimetry, carbon nanoparticles influence the crystallization behavior of the feedstock material significantly by acting as nucleation seeds, already at a few percent of a monolayer coating, while showing no effect on the fast heating process. The difference in calorimetric properties and crystallization behavior between the additivation methods of different abrasive forces is discussed. The surface-additivated carbon nanoparticles significantly increase the crystalline area by up to a threefold and the crystallization rate by up to a hundredfold. Furthermore, they change the crystal growth from a typical two- to three-dimensional growth of spherulites to a one- to two-dimensional growth of ellipsoidal impinged lamellar structures. Between 0.005 vol% and 0.05 vol% of well-dispersed carbon nanoparticles should be added to polyamide 12 to trigger an anisotropic heterogeneous nucleation while avoiding agglomerates. Graphical abstract: Unlabelled Image Highlights: Comparison of two additivation methods for best dispersion of carbon nanoparticles on polyamide 12 powder particles' surface Calorimetric setups to emulate the heating and cooling phases of laser powder bed fusion of composite polymer powders Microscopic indication of the anisotropic nucleation effect of carbon nanoparticles on the crystallization of polyamide 12 Change of crystallization behavior and crystal formation due to minute quantities of carbon nanoparticles